2021
DOI: 10.1002/ccd.29501
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world experience of suture‐based closure devices: Insights from the FDA Manufacturer and User Facility Device Experience

Abstract: Objectives: We analyzed post-marketing surveillance data from the United States Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database for suture-based vascular closure devices (VCDs) -Perclose ProGlide (Abbott, Chicago, Illinois) and Prostar XL (Abbott). Background: Suture-based VCDs are mostly used for large-bore femoral arterial access-site closure. Real-world, contemporary experience on the most commonly reported complications and modes of failure associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Nonetheless, VCD failures are not uncommon (1–8%), 11 , 22 , 33 are associated with major vascular complications and, in turn, with a higher risk of in-hospital and short-term death. 8 Major vascular complications after TAVR are associated with increased rates of in-hospital and short-term death, 5–7 reflecting the morbidity and mortality of a bleeding event and of vascular surgery performed in an emergency setting. Therefore, it is important to understand the difference between the available VCDs and to highlight any benefit to optimize the outcomes after TAVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, VCD failures are not uncommon (1–8%), 11 , 22 , 33 are associated with major vascular complications and, in turn, with a higher risk of in-hospital and short-term death. 8 Major vascular complications after TAVR are associated with increased rates of in-hospital and short-term death, 5–7 reflecting the morbidity and mortality of a bleeding event and of vascular surgery performed in an emergency setting. Therefore, it is important to understand the difference between the available VCDs and to highlight any benefit to optimize the outcomes after TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, despite a trend towards smaller TAVR delivery systems, the ever-increasing operator experience and the wide use of VCDs, bleedings related to major vascular complications remain relatively common, even in a low-risk setting, 2 , 3 exerting a negative impact on mortality. 6 Considering that major vascular complications are often linked to VCDs failure, 7 , 8 in the present systematic review and network meta-analysis (NMA), we aimed at collecting and summarizing the available evidence on the performance of VCDs regarding clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several mechanisms of Perclose failure have been reported, with malfunction of the sutures being the most common mechanism, accounting for 25% of cases. 3 In this article, we describe a method for optimization of suture-mediated closure with the Perclose ProGlide™ system, using balloon counterpressure to facilitate and confirm delivery of the suture knot to the vessel.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 A recently published review of post marketing surveillance of suture-based VCDs revealed 827 reports of major complications with Perclose ProGlide (Abbott Cardiovascular; Abbott Park, IL) and 175 reports of major complications with Prostar XL (Abbott Cardiovascular; Abbott Park, IL). 5 The authors concluded that in real-world practice, suture-based VCDs were found to be associated with complications, including vascular injury, difficulties with the device itself, and even death. Also, it has been observed that because of limited experience of TFA in routine interventional cardiology practice where TRA is the default access, the incidence of groin and device closure complications has increased ("Campeau Radial Paradox,") 6 .…”
mentioning
confidence: 99%